2003
DOI: 10.1007/s10595-002-2537-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Viral Genotypes and Rejection Episodes on the Recurrence of Hepatitis C After Liver Transplantation

Abstract: Our findings showed the genotype 1b to result in a higher recurrence rate after OLT. On the other hand, rejection episodes were associated with a more rapid progression to graft cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…As expected, high viral load and HCV genotype 1 was associated with progressive hepatitis, both typical R-HCV and AIH-like [13]. We were unable to confirm the adverse outcome with genotype 1B, also probably due to a low number of cases [14,19].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…As expected, high viral load and HCV genotype 1 was associated with progressive hepatitis, both typical R-HCV and AIH-like [13]. We were unable to confirm the adverse outcome with genotype 1B, also probably due to a low number of cases [14,19].…”
Section: Discussionmentioning
confidence: 54%
“…Of these 61 with hepatitis, 24 cases (39.3%), about a quarter (26%) of the entire study group (n = 92) developed histologically confirmed progressive fibrosis over a median follow-up period of 1447 days (range, 673-2231 days). As reported in the literature, there are several factors that are associated with progressive hepatitis after LT in HCV patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that patients infected with genotypes 1b and 4 had the worst outcomes, while genotype 2 and 3 patients had less-severe disease recurrence. Sugo et al [19] reported a higher recurrence rate in patients infected with genotype 1b compared to other genotypes, including genotype 4. Others have suggested a worse outcome in genotype 4-infected patients; however, these studies are limited by their small number of genotype 4-infected patients [20].…”
Section: Discussionmentioning
confidence: 99%